Sociolinguistics: Language variation and change analysis in the lyric song of Billie Eilish “Birds of a Feathers” - Rahel Purba; Rotua Pakpahan; Riby Siboro; Netania Saragih; Tiarma Intan Marpaung (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to find the comprehension of language variation and change in the industry of music in the present time. This research focuses on how lyrics in the current situation have been varied in order and evolve overtime. This research qualitative descriptive method, specifically in the new resources to finding song in the present time changing and differ across social culture. This study explores language variation and changes within the contemporary music industry by conducting a qualitative descriptive analysis of the lyrics of Billie Eilish’s 2024 single